Mortality trend in women outside the breast cancer screening age group from 2000 to 2019 in Brazil (Research, Society and Development, 2022)
Breast cancer is the one with the highest incidence, prevalence and mortality rates among all neoplasms that affect women, with the exception of non-melanoma skin tumors. Aiming to analyze the mortality trend in women outside the breast cancer screening age group (ICD-10 C50), from 2000 to 2019 in Brazil. We present this exploratory time series study of deaths from breast cancer. All women residing in Brazil, between 15 and 49 years old, who died from ICD-10 C50 participated in the study. Data collected from DATASUS, and for the analysis of trends, the polynomial regression model was used. In the period, there were 62,519 deaths from breast cancer in women outside the screening range, among them, those who were married and with advanced education had a higher death rate, as well as in the South and Southeast regions. The trend was increasing in all regions of the country. We conclude that it is essential for the government to participate in containing this growth in deaths in search of alternatives that can both include more women and expand the age group in screening. It is also important to emphasize education and information on the subject, by women and health professionals, regarding the suspected signs and symptoms of breast cancer, as well as facilitating access to health services, extending working hours. services for women who work full-time.